Genetically Modified Mesenchymal Stromal/Stem Cells as a Delivery Platform for SE-33, a Cathelicidin LL-37 Analogue: Preclinical Pharmacokinetics and Tissue Distribution in C57BL/6 Mice - Vagif Ali oglu Gasanov; Dmitry Alexandrovich Kashirskikh; Victoria Alexandrovna Khotina; Arthur Anatolievich Lee; Sofya Yurievna Nikitochkina; Daria Mikhailovna Kuzmina; Irina Vasilievna Mukhina; Ekaterina Andreevna Vorotelyak; Andrey Valentinovich Vasiliev (Antibiotics)
Background: The genetic modification of mesenchymal stromal/stem cells (MSCs) to express antimicrobial peptides may provide a promising strategy for developing advanced cell-based therapies for bacterial infections, including those caused or complicated by antibiotic-resistant bacteria. We have previously demonstrated that genetically modified Wharton’s jelly-derived MSCs expressing an antimicrobial peptide SE-33 (WJ-MSC-SE33) effectively reduce bacterial load, inflammation, and mortality in a mouse model of Staphylococcus aureus-induced pneumonia compared with native WJ-MSCs. The present study aimed to evaluate the pharmacokinetics and tissue distribution of the SE-33 peptide expressed by WJ-MSC-SE33 following administration to animals. Methods: WJ-MSC-SE33 were administered to C57BL/6 mice at therapeutic and excess doses. The biodistribution and pharmacokinetics of the SE-33 peptide were analyzed in serum, lungs, liver, and spleen using chromatographic methods after single and repeated administrations. Results: The SE-33 peptide exhibited dose-dependent pharmacokinetics. The highest levels of SE-33 peptide were detected in the liver and lungs, with persistence in tissues for up to 48 h at medium and high doses of administered WJ-MSC-SE33. A repeated administration of WJ-MSC-SE33 increased SE-33 levels in target organs. Conclusions: The SE-33 peptide expressed by genetically modified WJ-MSCs demonstrated predictable pharmacokinetics and effective biodistribution. These findings, together with the previously established safety profile of WJ-MSC-SE33, support its potential as a promising cell-based therapy for bacterial infections, particularly those associated with antibiotic resistance.